MODIFICATION LEAF DREGS OF LEMONGRASS WITH CITRIC ACID FOR Cd(II) REMOVAL - Rahmiana Zein; Syiffa Fauzia; Mutiara Suciandica (JURNAL KATALISATOR, 2022)
The present research was studied the capability of leaf dregs lemongrass (LDLG) and modified LDLG by Citric Acid (LDLGCA) for Cd(II) removal.  The optimum conditions for both biosorbents at pH 5, stirring speed 200 rpm, contact time 60 minutes, and temperature 25 ᵒC. The optimum concentration LDLG was 120 mg/L and 160 mg/L  LDLGCA with adsorption capacity 10.63 mg/g and 11.66 mg/g, respectively. Isotherm models revealed that the adsorption of LDLG and LDLGCA followed Langmuir isotherm model with coefficient determination (R2) 0.98 LDLG and 0.93 LDLGCA. Both biosorbents were fitted to pseudo-second-order indicating that adsorption process chemically occurring. Adsorption Cd(II)  LDLG spontaneous reactions and exothermic, meanwhile for Cd(II) removal LDLGCA not spontaneous and exothermic. The characterization biosorbents was done using  FTIR, XRF, SEM – EDX and BET. The adsorption capacity of both biosorbents decreased after 3 times adsorption-desorption cycles. Applications biosorbents to the real wastewater (Laboratory wastewater)  indicated that LDLG can remove Cd(II) up to 46.88 % and  LDLGCA reached the peak at  52.14 %. Based on XRF data, the percentage of Cd(II) in both adsorbents increased up to 21.12% for LDLG and 24.04 % for LCGA. The result indicated that Citric Acid was quite effective as modifier for Cd(II) removal.